Effect of Land Agricultural Fertilizer on Growth of Marine Single Cell Protein, Spirulina platensis, Chlorella vulgaris and Nannochloropsis - Purnama Sukardi; Ferisa Wahyunika; Tjahyo Winanto; Norman Arie Prayogo; Taufan Harisam; Arif Mahdiana; Sri Marnani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
This study aimed to determine the growth rate and protein content in Nannochloropsis oculata, Chlorella vulgaris, Spirulina platensis were cultured using agricultural fertilizers. The agricultural fertilizers used were Urea, ZA and TSP. Each single cell protein was cultured using the three types of fertilizers with a ratio of Urea: ZA and TSP as follows (A) 1: 2: 1 [(10:20:10 g / L)], (B) 2: 2: 1 [(20:20:10 g / L)] and (C) 3: 2: 1 [(30:20:10 g / L)], respectively. The results showed that the best ratio of Urea, ZA and TSP fertilizers to growth of Spirulina, Nannochloropsis oculata and Chlorella vulgaris was C [30:20:10 (g / L)] treatment. However, phyto-protein content in Nannochlorophsis differed significantly between fertilization treatments, C fertilization yielded the highest protein content (28.75±0.05%), when compared with A (25.13±0.01%) and B (25.14±0.02%), respectively. In Chlorella vulgaris, all fertilization treatments showed very significant differences, B fertilization (28.24%±00.006) yielded the highest phyto-protein content, if compared to A (23.63% ± 0.003) and C (19.74% ±0.006 ), respectively. All fertilization treatments showed very significant differences (P <0.05) on Spirulina platensis. The highest content of phyto-protein (62.68 + 0.05%) was present in treatment C, when compared to A (52.18 + 0.05%) and B (62.37 + 0.01%) treatments, respectively.